PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA ROMAKU (RODA MASSA DAN KUANTITAS) UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR - Anggraini, Dwi; Rohim, Abdur (PHI: Jurnal Pendidikan Matematika, 2026)
Elementary school students' numeracy skills are still low, influenced by the abstract nature of mathematics and the use of less interesting learning media. This study aims to design and develop a mathematics learning media called ROMAKU (Roda Massa dan Quantitas), and evaluate its level of validity, practicality, and effectiveness in improving students' numeracy skills. The study used a Research and Development (R&D) approach with a 4D model, including the define, design, develop, and disseminate stages; but limited to the develop stage. Participants were fifth-grade elementary school students. Data were obtained through validation sheets, questionnaires, observations, and numeracy tests (pre-test and post-test). The results showed that ROMAKU media had a validity score of 89.75% (very valid), practicality of 90% (very practical), and effectiveness with 80% of students achieving learning mastery. Thus, ROMAKU media is feasible and effective for improving students' numeracy skills, especially in the concept of mass and quantity.